Rancang Bangun Website Berbasis CMS Wordpress Versi 6.3 di Kampung Kalamanuk Distrik Fakfak Timur Tengah - Maria Marlince Weripang; Indri Anugrah Rahmadhani; Matahari Matahari (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
Village information still uses madding, making it difficult for residents to get accurate information. The aim of this research is to produce a WordPress CMS-based website in Kalamanauk Village, Fak-fak District, Middle East and a website that is valid, practical and effective to use. This research method uses the Research and Development (R&D) development method. Data was collected by observation, interviews, literature studies and questionnaires. The subjects of this research were 20 people from the Kalamanuk village, Middle East Fakfak district. Descriptive statistical data analysis techniques for presenting data using tables and calculating averages. Based on the results that the researchers have obtained, they obtained validation results from 1 validator, including website experts, namely the average percentage, namely an average percentage of 95%, which is referred to in the "Very valid" criteria. The level of practicality of the village website was obtained from the respondent questionnaire, the results obtained were an average percentage of 90% which was referred to in the "Very practical" criterion, the level of effectiveness of the website was obtained from the respondent questionnaire, the results obtained were an average percentage of 86% which was referred to in the criterion " Very effective". Based on the results of the respondent's trial, an average score of 87% was obtained in the "Very good" category. The results of this research show that the WordPress CMS-based website design is valid, practical and effective to use.